2021
DOI: 10.3390/s21238020
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Explainable Artificial Intelligence for Prognostic and Health Management of Industrial Assets Based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses

Abstract: Surveys on explainable artificial intelligence (XAI) are related to biology, clinical trials, fintech management, medicine, neurorobotics, and psychology, among others. Prognostics and health management (PHM) is the discipline that links the studies of failure mechanisms to system lifecycle management. There is a need, which is still absent, to produce an analytical compilation of PHM-XAI works. In this paper, we use preferred reporting items for systematic reviews and meta-analyses (PRISMA) to present a state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 118 publications
0
21
0
Order By: Relevance
“…PHM-XAI is still a very young discipline. As testified by the recent systematic review on PHM-XAI presented in [39] and shown in Figure 2(a), several peer reviewed journal articles treating the subject is still small but steadily rising. Several explainability approaches have been explored by the PHM-XAI researchers.…”
Section: Promote Interactivity and Expand Human Creativity By Discove...mentioning
confidence: 91%
See 2 more Smart Citations
“…PHM-XAI is still a very young discipline. As testified by the recent systematic review on PHM-XAI presented in [39] and shown in Figure 2(a), several peer reviewed journal articles treating the subject is still small but steadily rising. Several explainability approaches have been explored by the PHM-XAI researchers.…”
Section: Promote Interactivity and Expand Human Creativity By Discove...mentioning
confidence: 91%
“…While the explanation fulfils several demanded general qualities, the need to evaluate explanation based of PHM criteria such as security and safety, cost, and time are still present. This aspect is also echoed in [39]. Therefore, it is crucial for PHM-XAI researchers to develop explanation metrics satisfying PHM needs.…”
Section: Safeguarding Security and Explanation Evaluationmentioning
confidence: 94%
See 1 more Smart Citation
“…The review presented in [44] further lists several deficiencies plaguing the research in PHM-XAI that need to be remedied promptly, considering:…”
Section: Research Gaps and Opportunitiesmentioning
confidence: 99%
“…In recent years, AI has become a predominant tool in reliability-based research [43]. PHM-XAI is still a very young discipline as testified by the recent systematic review on PHM-XAI presented in [44] and shown in Figure 2a, where several peer-reviewed journal articles treating the subject demonstrate that the PHM-XAI is still scarcely studied but steadily rising. Several explainability approaches have been explored by the PHM-XAI researchers.…”
Section: Introduction 1artificial Intelligencementioning
confidence: 99%